Penerapan Asas Keadilan, Kemanfaatan, dan Kepastian Hukumdalam Kebijakan Pengampunan Pajak (Tax Amnesty) di Indonesia - Yesi Arfianto (Wijayakusuma Law Review, 2021)
The purpose of this study is to determine the application of the principles of justice, benefit, and legal certainty intax amnesty policies in Indonesia. There are many problems in society related to the absence of the principle ofjustice and the principle of legal certainty in the implementation of tax amnesty policies based on Law Number11 of 2016 concerning Tax Amnesty. This study uses a descriptive normative type of research based on thematerials collected, both primary and secondary legal materials. The research approach used by the author is astatutory approach. The results of the study stated that the principle of justice and the principle of legal certaintycould not be applied optimally, however, the principle of benefit could be implemented properly with theimplementation of a tax amnesty program properly.